2023
DOI: 10.1002/jad.12263
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone and social network addiction in early adolescents: The role of self‐regulatory self‐efficacy in a pilot school‐based intervention

Ainzara Favini,
Flavia Culcasi,
Flavia Cirimele
et al.

Abstract: BackgroundYouths' online problematic behaviors, such as smartphone or social network sites (SNS) addiction, gained increasing attention nowadays, due to their impact on concurrent and later adjustment, such as emotional and/or behavioral problems, academic impairments, or relational issues.AimsThis study aims to evaluate the effectiveness of a pilot school‐based intervention to contrast online addictive behaviors while fostering adolescents' self‐regulative abilities.Materials & MethodsThe intervention sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…By contrast, initiatives that rely on parents, teachers, or clinicians, while potentially easier to tailor to the individual needs and circumstances of each adolescent, can be expensive to roll out, whether through training or awareness raising or other public outreach, as well as difficult to sustain and, too often, taken up more by privileged than neglected segments of society. For example, Favini et al (2023) design a school intervention to enhance adolescent self-efficacy to combat what they term social media "addiction." This illustrates well the challenge for public policymakers: would they do better to fund annual, nationwide, school-based interventions to prevent excessive use of social media or, instead, should they develop regulation to restrict digital platforms' use of certain design features shown to be compulsive (such as personalized algorithms or endless scroll and autoplay in video feeds or lootboxes in gaming).…”
Section: Who Should Act On Findings About Adolescents' Digital Lives?mentioning
confidence: 99%
“…By contrast, initiatives that rely on parents, teachers, or clinicians, while potentially easier to tailor to the individual needs and circumstances of each adolescent, can be expensive to roll out, whether through training or awareness raising or other public outreach, as well as difficult to sustain and, too often, taken up more by privileged than neglected segments of society. For example, Favini et al (2023) design a school intervention to enhance adolescent self-efficacy to combat what they term social media "addiction." This illustrates well the challenge for public policymakers: would they do better to fund annual, nationwide, school-based interventions to prevent excessive use of social media or, instead, should they develop regulation to restrict digital platforms' use of certain design features shown to be compulsive (such as personalized algorithms or endless scroll and autoplay in video feeds or lootboxes in gaming).…”
Section: Who Should Act On Findings About Adolescents' Digital Lives?mentioning
confidence: 99%
“…Another set of studies address the role of interventions to support adaptive use of digital technologies. The study by Favini et al (2024) evaluated the effectiveness of pilot school‐based interventions to tackle online addictive behaviors in a sample of 462 Italian 14–16 year olds. Results confirmed the short‐term effectiveness of their intervention, in particular a significant buffering effect of self‐regulatory self‐efficacy beliefs, highlighting the importance to develop relevant agentic behaviors among young people to reduce online problematic behaviors.…”
Section: Adolescents' Digital Livesmentioning
confidence: 99%
“…The study by Van de Casteele et al (2024) identified satisfaction of basic psychological needs for autonomy, competence, and relatedness both offline and online as significant predictors of adolescent mental health, although offline need satisfaction played a more crucial role in their samples of adolescents and in particular among emerging adults in Belgium.Another set of studies address the role of interventions to support adaptive use of digital technologies. The study by Favini et al (2024) evaluated the effectiveness of pilot school-based interventions to tackle online addictive behaviors in a sample of 462 Italian 14-16 year olds. Results confirmed the short-term effectiveness of their intervention, in particular a significant buffering effect of self-regulatory self-efficacy beliefs, highlighting the importance to develop relevant agentic behaviors among young people to reduce online problematic behaviors.In a sample of 1018 Austrian adolescents Strohmeier et al ( 2024) addresses the digital gender gap.…”
mentioning
confidence: 99%